Dual microelectrodes decorated with nanotip arrays: Fabrication, characterization and spectroelectrochemical sensing. (20th December 2019) - Bombail, Thibault; Garrigue, Patrick; Goudeau, Bertrand; Talaga, David; Bouffier, Laurent; Bonhommeau, Sébastien; Servant, Laurent; Zigah, Dodzi; Arbault, Stéphane; Sojic, Neso
Abstract: Gold microelectrodes decorated with nanotips were developed for spectroelectrochemical experiments. These new dual probes were fabricated by combining fabrication processes of scanning near-field optical microscopy with photolithography. A nanotip array was produced at the surface of a coherent optical fiber bundle by a wet chemical etching step. The resulting nanostructured surface was sputter-coated with a thin gold layer. This gold film conferred plasmonic properties to the sharp nanotips and served as well as the electrode material to enable electrochemical reactions. A photolithographic process was used to delimit on the bundle surface nanotips-decorated microelectrodes with tunable dimensions (radii ranging between 20 μm and 3.5 μm) individually or in an array format. The resulting microelectrodes with a regular nanotip pattern were characterized first by cyclic voltammetry. Numerical simulation was used to assess the electrochemical properties of these platforms and the influences of the recessed geometry and of the nanotips. Approach curves were recorded in negative and positive feedback modes of scanning electrochemical microscopy (SECM) on insulating and conducting substrates. Finally, spatially resolved Raman imaging allowed us to detect a mercaptobenzoic acid monolayer adsorbed on the microelectrode surface, demonstrating a surface-enhanced Raman scattering (SERS) effect induced by the gold-coated nanotips with a typical enhancement factor of ∼7 × 10 4 . Such an approach introduces a reproducible method to fabricate promising SERS-active platforms with microelectrode behavior for SECM experiments.